How thiopurines are used for the treatment of inflammatory bowel diseases: An Italian survey. Issue 2 (February 2015) - Saibeni, Simone; Kohn, Anna; Meucci, Gianmichele; Papi, Claudio; on behalf of the Italian Group for Inflammatory Bowel Disease (IG-IBD)
Abstract Background The ideal manner of thiopurine use in inflammatory bowel disease has not been defined. We aimed at investigating the attitudes of Italian gastroenterologists on thiopurine use. Methods A web-based survey was performed among 295 gastroenterologists. Results Overall, 70 surveys were completed. At baseline, thiopurine methyltransferase genotype and phenotype were not assessed by 87.1% and 97.1% of respondents, respectively. At treatment onset, 17.1% adopted full weight-calculated dose while 80.0% preferred escalating the dose. During treatment, 87.1% and 64.3% reduced the dose for myelo- and liver toxicity, respectively; 48.6% for increased pancreatic enzymes, 17.1% for fever, and 5.7% for arthralgia. A systematic shift from one thiopurine to the other was reported by 4.3% of respondents in case of failure, and by 5.7% for adverse effects. Forty-four gastroenterologists (62.9%) stopped thiopurine treatment after 5–7 years. Conclusions Several discrepancies regarding the use of thiopurines in clinical practice were found, deviating from available guidelines. A more standardised attitude is needed in clinical practice.